PEMANFAATAN TEPUNG KACANG MERAH DAN PATI SAGU PADA PEMBUATAN CRACKERS - Weni Mulyani Asfi; Noviar Harun; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to the best obtain the ratio of red bean flour and sago starch selected in the making of crackers. This research used Complete Randomized Design (CRD) with 6 treatments and 3 replications which were followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in this research included K0S0 (ratio of red bean flour and sago starch 100 : 0), K1S1 (ratio of red bean flour and sago starch 90 : 10), K2S2 (ratio of red bean flour and sago starch 80 : 20), K3S3 (ratio of red bean flour and sago starch 70 : 30), K4S4 (ratio of red bean flour and sago starch 60 : 40), and K5S5 (ratio of red bean flour and sago starch 50 : 50). The result of analysis showed that the ratio of red bean flour and sago starch significantly affect on water content, ash content, protein content, and sensory test. The best treatment crackers was K5S5 with water content (2,33%), ash content (2,18%), protein content (8,57%), and sensory test with colour of yellowish brown, flavorful red beans and sago starch, a little taste of red beans and sago starch, crunchy texture, and overall assesment of crackers was preferred by the panelist. Keywords: crackers, red bean flour and sago strach